Competence Strengthening of Hard Skills and Soft Skills of Prospective Religious Education Teacher Students through the Introduction to School Field Program (PLP) in Indonesia - Muh Hizbul Muflihin; Arif Budi Raharjo; Hanif Cahyo Adi Kistoro; Khairul Hamimah Mohamad Jodi (Jurnal Pendidikan Agama Islam, 2024)
Purpose – The Introduction to School Field Program (PLP) in Indonesia is mandatory in universities and designed to produce professional teacher candidate competencies. Each prospective teacher-student is equipped with adequate hard skills and soft skills before becoming a teacher in the school environment. Design/methods/approach – This study used a phenomenological approach that aims to obtain an understanding of the hard skills and soft skills taught in the PLP program. Moreover, the study also explained what types of hard skills and soft skills were trained during the PLP. This phenomenological research explored the experience of prospective teacher students participating in PLP. The research data was taken through in-depth interviews with interview guidelines made for 20 PLP participating students at the two host universities in Purwokerto and the Special Region of Yogyakarta. Data analysis used data reduction, presentation, and interpretation. Findings – The study results found that the teaching of hard skills and soft skills has been integrally applied in the program through the existing curriculum. Methods of mentoring, field practice, evaluation, and improvement have been used in the PLP program. Meanwhile, the types of hard and soft skills provided consist of ethics, communication, learning design, and evaluation making. Research implications/limitations – The respondents of this study were limited to the coverage of two regions, namely Central Java and the Special Region of Yogyakarta, leading to the research limitation. Expanding the research location and using other quantitative research can strengthen the results of this study. Originality/value – Future studies should further overcome the shortcomings of this program and improve to be reference for policy-making by the PLP program organizers.